The Impact of Entrepreneurial Marketing, Relational Marketing and Innovation Strategy on Marketing Performance Business - Laili Savitri Noor (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The purpose of this study is to analyze and discuss the impact of Entrepreneurial Marketing, Relational Marketing and Innovation Strategy on the Marketing Performance of Batik Businesses in Central Java. This research method uses a causal-verification method with a survey technique, and data processing is carried out using Structural Equation Modeling–Partial Least Squares (SEM-PLS) on 126 batik business units selected through a purposive sampling technique. The results of the study indicate that innovation strategy has a significant effect on marketing performance (KP), while relational marketing plays an indirect role by strengthening the innovation process. Customer knowledge has also been shown to be a key factor driving SI and KP, reinforcing the importance of market understanding in strategic decision making. However, the effectiveness of innovation is greatly influenced by the industry context, product type, and marketing approach used. This shows that there is no single strategy that applies universally. These findings emphasize the need for a contextual and adaptive marketing model, in line with the dynamics typical of batik SMEs. Integration between entrepreneurial, relational, and innovative approaches is key to improving competitiveness, customer satisfaction, and long-term sustainability of the batik industry.